Changes in mouse cognition and hippocampal gene expression observed in a mild physical- and blast-traumatic brain injury - David Tweedie; Lital Rachmany; Vardit Rubovitch; Yongqing Zhang; Kevin G. Becker; Evelyn Perez; Barry J. Hoffer; Chaim G. Pick; Nigel H. Greig (Neurobiology of Disease, 2013)
Warfare has long been associated with traumatic brain injury (TBI) in militarized zones. Common forms of TBI can be caused by a physical insult to the head–brain or by the effects of a high velocity blast shock wave generated by the detonation of an explosive device. While both forms of trauma are distinctly different regarding the mechanism of trauma induction, there are striking similarities in the cognitive and emotional status of survivors. Presently, proven effective therapeutics for the treatment of either form of TBI are unavailable. To be able to develop efficacious therapies, studies involving animal models of physical- and blast-TBI are required to identify possible novel or existing medicines that may be of value in the management of clinical events. We examined indices of cognition and anxiety-like behavior and the hippocampal gene transcriptome of mice subjected to both forms of TBI. We identified common behavioral deficits and gene expression regulations, in addition to unique injury-specific forms of gene regulation. Molecular pathways presented a pattern similar to that seen in gene expression. Interestingly, pathways connected to Alzheimer's disease displayed a markedly different form of regulation depending on the type of TBI. While these data highlight similarities in behavioral outcomes after trauma, the divergence in hippocampal transcriptome observed between models suggests that, at the molecular level, the TBIs are quite different. These models may provide tools to help define therapeutic approaches for the treatment of physical- and blast-TBIs. Based upon observations of increasing numbers of personnel displaying TBI related emotional and behavioral changes in militarized zones, the development of efficacious therapies will become a national if not a global priority.